(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article considers the problems of the formation of the energy security system of the Eurasian Economic Union at the present stage of development of this organization in the context of formation power the politician and energy strategies of countries of the EEU. The focus of the research is on the issue of creating a single energy market as a key factor in overcoming interstate and interstate contradictions in the structure and reserves of the energy systems of the member countries of the Union. The specified problems are analyzed in the context of the interests of both national states and the general goals of the organization. It is noted that at this stage of the development of the Unified Energy System, a single energy market, which many profile experts often call the Union’s unified power system, is more of a declarative nature than a practical one. At the same time, almost all specialists in this field note the unconditional economic and other benefits from its creation and further functioning in the Eurasian space. Key words: Eurasian Economic Union, energy security, integration, single energy market.